Compendium of International and National Legal Frameworks on Female Genital Mutilation, Fifth Edition - World Bank (World Bank, Washington, DC, 2021)
Female Genital Mutilation/Cutting (FGM/C) is a development issue and a form of violence against women and girls that affects at least 200 million women in the world. FGM/C is a harmful practice proven to impact the physical and mental health of affected women and girls from the moment of the cutting, with prolonged and irreversible consequences during their entire lives. The Compendium on International and National Legal Frameworks on Female Genital Mutilation (the "Compendium") was prepared to contribute to this urgent and important development debate with the understanding that the knowledge of the law is an important empowerment tool to end FGM/C It provides a survey of the key international and regional instruments as well as domestic legislation as they relate to the prohibition of FGM/C.